HUBUNGAN DISIPLIN DENGAN KINERJA PEGAWAI - Chusminah, Chusminah (Economic Faculty, Attahiriyah Islamic University, 2019)
The aim of the study is to determine the effect of work discipline on the performance of employees.The type of research used is explanatory research with a quantitative approach. The sample in this study was 40 respondents using convenience sampling techniques. Respondents in the sample were civil servants in the Sub Directorate of Civil Service Archives II.B at the Jakarta State Civil Service Agency. The findings in this study indicate that there is an influence of work discipline on performance. This is indicated by the results of the calculation of the correlation coefficient of r = 0.823. The results of this study are strengthened by the results of the calculation of the coefficient of determination which proves that the variable work discipline has a significant effect of 67.8%, while the remaining 32.2% is influenced by other factors that do not count in this study.